1998
DOI: 10.1002/hlca.19980810513
|View full text |Cite
|
Sign up to set email alerts
|

β2‐ and β3‐Peptides with Proteinaceous Side Chains: Synthesis and solution structures of constitutional isomers, a novel helical secondary structure and the influence of solvation and hydrophobic interactions on folding

Abstract: Enantiomerically pure a-amino-acid derivatives with the side chains of A h , Val, and Leu in the 2-or 3-position (8'-and P3-amino acids, resp.), as well as with substituents in both the 2-and 3-positions (Pz.3-amino acids, of like-configuration) have been prepared (compounds 8-17) and incorporated (by stepwise synthesis and fragment coupling, intermediates 24-34) into P-hexa-, P-hepta-, and j-dodecapeptides (1 -17). The new and some of the previously prepared P-peptides (35-39) showed NHiND exchange rates (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
347
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 351 publications
(361 citation statements)
references
References 55 publications
10
347
2
2
Order By: Relevance
“…The biggest breakthrough in the synthesis β-peptides of defined sequence that allowed crystallographic and high-resolution NMR data to be obtained was achieved by the research groups of Gellman [10]- [15] and Seebach [16]- [19]. Gellman and co-workers have synthesized and characterized the oligomers of trans-2-aminocyclo-pentanecarboxylic acid (ACPC) [12], trans-2-aminocyclohexanecarboxylic acid (ACHC) [11] and trans-3-aminopyrrolidine-4-carboxylic acid (ACP) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biggest breakthrough in the synthesis β-peptides of defined sequence that allowed crystallographic and high-resolution NMR data to be obtained was achieved by the research groups of Gellman [10]- [15] and Seebach [16]- [19]. Gellman and co-workers have synthesized and characterized the oligomers of trans-2-aminocyclo-pentanecarboxylic acid (ACPC) [12], trans-2-aminocyclohexanecarboxylic acid (ACHC) [11] and trans-3-aminopyrrolidine-4-carboxylic acid (ACP) [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Oligomers containing both ACPC and ACP residues were also shown to form 12-helical conformations in aqueous solution [15]. Seebach and co-workers showed that β-peptides composed of acyclic residues with side chains derived from α-amino acids also formed 14-helical conformations in organic solvent [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of beta peptides by Seebach et al [21], their propensity to fold into stable secondary structures has been successfully used to mimic secondary structures, such as helices [6,7,9,20,22], sheets [19] or turns [23]. Furthermore, beta peptides show a remarkable metabolic stability making them attractive candidates for peptidomimetic design.…”
Section: Introductionmentioning
confidence: 99%
“…7 The cyclic side-chain of the latter lends extra stability to the secondary structure through the restricted conformational space and the i-(i+3) hydrophobic stacking interactions between the cyclohexane rings. 8 Recent results led to the successful synthesis of monoterpene-derived b-amino acids with an apopinane skeleton (2-amino-6,6-dimethyl-bicyclo[3.1.1]heptane-3-carboxylic acid; ABHC). 9 The apopinane moiety is a dimethyl-substituted, methylene-bridged analog of ACHC and, as such, further enhances the conformational preorganization of the cyclohexane ring, but the bulky substituent certainly disfavors the i-(i+3) hydrophobic stacking interactions in H14 (Fig.…”
mentioning
confidence: 99%